Medium-Intensity Treadmill Exercise Exerts Beneficial Effects on Bone Modeling Through Bone Marrow Mesenchymal Stromal Cells - Zhang, Lingli; Yuan, Yu; Wu, Wei; Sun, Zhongguang; Lei, Le; Fan, Jing; Gao, Bo; Zou, Jun (Frontiers in Cell and Developmental Biology, 2020)
As a type of multipotential cells, bone marrow mesenchymal stromal cells (BMMSCs) can differentiate into chondrocytes, osteoblasts, and adipocytes under different loading condition or specific microenvironment. Previous studies have shown that BMMSCs and their lineage-differentiated progeny (for example, osteoblasts), and osteocytes are mechanosensitive in bone. The appropriate physical activity and exercise could help attenuate bone loss, effectively stimulate bone formation, increase bone mineral density (BMD), prevent the progression of osteoporosis, and reduce the risk of bone fractures. Bone morphogenetic protein (BMP) is originally discovered as a protein with heterotopic bone-inducing activity in the bone matrix that exerts a critical role in multiple stages of bone metabolism. In the present study, the medium-intensity treadmill exercise suppressed bone resorption, enhanced bone formation and increased osteocalcin (OCN) and osteopontin (OPN) mRNA expression as well as activation of the BMP-Smad signaling pathway in vivo. In addition, LDN -193189HCL, an inhibitor of SMAD 1/5/8 phosphorylation by BMP increased the serum levels of calcium and phosphorus in mice and attenuated the BMD and bone mass mediated by medium-intensity exercise and BMP-Smad signaling pathway. Taken together, these results suggested the involvement of BMP-Smad signaling pathway in the beneficial effect of exercise-induced BMD and bone mass in mice.